2021
DOI: 10.17645/si.v9i2.3850
|View full text |Cite
|
Sign up to set email alerts
|

Daily Mobility Patterns: Reducing or Reproducing Inequalities and Segregation?

Abstract: Theory states that residential segregation may have a strong impact on people’s life opportunities. It is unclear, however, to what extent the residential environment is a good representation of overall exposure to different people and environments. Daily mobility could reduce the negative effects of segregation if people change environments and/or become more mixed. They could also enhance existing segregation patterns if daily mobility produces more segregated environments. This article uses mobile phone dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 46 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…We record the antenna locations and duration of stay (in 5-min intervals) for each pseudonymised phone over a 24 h window separately for each of the three years (see also Hedman, Kadarik, Andersson, & Östh, 2021 ; Östh, Shuttleworth, & Niedomysl, 2018 ). MIND contains a scrambled IMSI code (unique identifier for each SIM-card) that can be used to separate users.…”
Section: Empirical Framing Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We record the antenna locations and duration of stay (in 5-min intervals) for each pseudonymised phone over a 24 h window separately for each of the three years (see also Hedman, Kadarik, Andersson, & Östh, 2021 ; Östh, Shuttleworth, & Niedomysl, 2018 ). MIND contains a scrambled IMSI code (unique identifier for each SIM-card) that can be used to separate users.…”
Section: Empirical Framing Of the Researchmentioning
confidence: 99%
“…However, the precision of the location is conditioned on the density of antennas, which means that phones in urban areas and in proximity to infrastructure hubs are localized with greater precision compared to phones in rural areas, since the density of antennas is greater in population dense areas. In this study, we estimate the location of phones using two main steps: We record the antenna locations and duration of stay (in 5-min intervals) for each pseudonymised phone over a 24 h window separately for each of the three years (see also Hedman, Kadarik, Andersson, & Östh, 2021 ; Östh, Shuttleworth, & Niedomysl, 2018 ). MIND contains a scrambled IMSI code (unique identifier for each SIM-card) that can be used to separate users.…”
Section: Empirical Framing Of the Researchmentioning
confidence: 99%
“…A majority of the works that were found through our systemic literature review was produced by or in collaboration with researchers in fields such as computer or information sciences. Whilst there has been some works produced within the fields of social science, such as Ahas et al (2015), Eagle et al (2010), Hedman et al (2021), andÖsth et al (2018), they are a minority in our sample. Nevertheless, these researchers have produced insights in a number of social phenomena with relatively straightforward incorporation of mobile phone data in the methodological framework.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…A set of studies used mobile phone data to assess questions of segregation, which leaves a clear trail in communication and mobility patterns (Hedman et al 2021;Östh et al 2018). For instance, Cottineau and Vanhoof (2019) found that mobility range and diversity tended to decrease in cities with large levels of segregation.…”
Section: Aggregate Patterns Of Human Mobility and Social Networkmentioning
confidence: 99%
See 1 more Smart Citation